β-Arrestin 2 Promotes Hepatocyte Apoptosis by Inhibiting Akt Pathway in Alcoholic Liver Disease - Sun, Ying-Yin; Zhao, Yu-Xin; Li, Xiao-Feng; Huang, Cheng; Meng, Xiao-Ming; Li, Jun (Frontiers in Pharmacology, 2018)
Alcoholic liver disease (ALD) is a complex process that includes a wide range of hepatic lesions, from steatosis to cirrhosis, and even worse, it may cause the hepatocellular carcinoma (HCC). So far, evidences has now accumulated showing that the cytotoxic effects of ethanol metabolism lead to cell apoptosis and necrosis in ALD. Recently, several studies reveal that multifunctional protein β-arrestin2 (Arrb2) modulates cell apoptosis in liver fibrosis and HCC, but its role in ALD has not been investigated. The aim of this study is to explore that whether Arrb2 involved in the process of cell apoptosis, and the role of AKT signaling pathway associated with hepatocyte survival and apoptosis in ALD. In our study, the hepatocyte which were isolated from the liver tissue of C57BL/6 mice fed EtOH-containing diet showed an increasing expression of Arrb2.Meanwhile, EtOH significantly up-regulated Arrb2 production in AML-12 cells in vitro. Futhermore, TUNEL and FCM results demonstrated that siRNA Arrb2 could inhibit hepatocyte apoptosis induced by EtOH in vivo and vitro while over-expression of Arrb2 had an opposite effect on apoptosis in ALD. In addition, Western blot results revealed thatArrb2 remarkably inhibited the expression of p-Akt. Therefore, our data suggest that Arrb2 promotes hepatocyte apoptosis by inhibiting Akt signaling pathway that Arrb2 may be a potential therapeutic target for ALD.